P247 Impact of Implementing COPD Self Management Plans & Rescue Medications Across 3 Hospitals. (19th November 2012) - Khachi, H; Hodson, M; Welsby, V; Hudson, R; Roberts, CM
Abstract : Introduction: COPD is the second leading cause of emergency admissions in the UK. National guidelines for managing COPD advise that patients at risk of having or those who have had an exacerbation of COPD should be given self-management advice that encourages them to respond promptly to their symptoms. As part of this, they should be given a course of oral antibiotics and corticosteroids to keep at home for use in the event of an exacerbation. Whilst this approach is established with a strong evidence base in asthma, evidence suggestive that this is effective in reducing hospital admissions and readmissions in COPD is inconsistent. 1 Aims and Objectives: This study aims to assess the impact of implementing a unified self management strategy, consisting of self management plan, education and rescue medications, in reducing hospital inpatient readmissions at 30 and 90 days. Methods: The study was carried out over six months, across three acute hospitals, between November 2010 and April 2011. All patients admitted with a primary diagnosis of COPD exacerbation were included and given the following unless there were any contra-indications for providing this: A unified written self management plan Rescue medication of a 7 day course of prednisolone and 5 day course of antibiotic Education on self management and how to use their rescue medication To assess the impact of the self management strategy, data was collected for both patients who did and did not receive this intervention. For the purpose of accuracy, 10% of data was cross-checked by an independent person. Results: During the 6 month audit period, 457 patients with acute hospital admission for COPD exacerbation were recruited, with 68%, 54.6% and 24.5% (mean 40.1%) of patients at each of the 3 sites receiving a self management plan and rescue medication. Main reasons for not receiving included patients not speaking English, couldn't understand self management advice or refused to self manage. Conclusions: Self management and rescue medication is associated with a reduction in 30 and 90 day readmission rates by 12.5% and 4.3% respectively. A high proportion of patients did not receive these for practical reasons which need addressing for future evaluations. References: Walters JAE, Turnock AC, Walters EH et al. Action plans with limited patient education only for exacerbations of chronic obstructive pulmonary disease. Cochrane Database of Systematic Reviews issue 5: CD005074. 2010.